2014
DOI: 10.1111/jgs.12926
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Communication in End‐of‐Life Care: A Clinical Tool Translating Between the Clinical Frailty Scale and the Palliative Performance Scale

Abstract: This conversion chart is a reliable means of translating scores between the CFS and PPS and is useful for geriatric and palliative care teams collaborating in the care of elderly adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…34 Another study reported a CFS-weighted kappa of 0.92. 35 Another limitation of CFS in our center is the significant proportion of missing data (28%). As we have shown, missing CFS data are more frequent in situations of very high acuity (including in critical care or surgical areas) or in medical areas when the LOS was short (eg, less than 72 hours).…”
Section: Discussionmentioning
confidence: 96%
“…34 Another study reported a CFS-weighted kappa of 0.92. 35 Another limitation of CFS in our center is the significant proportion of missing data (28%). As we have shown, missing CFS data are more frequent in situations of very high acuity (including in critical care or surgical areas) or in medical areas when the LOS was short (eg, less than 72 hours).…”
Section: Discussionmentioning
confidence: 96%
“…Fifth, frailty assessments could have been performed by 2 raters to increase reliability and prevent misclassification. However, the tool used showed high interrater reliability in a previous study [ 37 ]. Finally, the data should be interpreted with caution due to the small number of participants in the frailest group.…”
Section: Discussionmentioning
confidence: 97%
“…As this study was conducted in a real world setting, we were unable to obtain inter-rater reliability. The CFS has previously been demonstrated to have high inter-rater reliability [ 11 , 26 ].…”
Section: Discussionmentioning
confidence: 99%